An evaluation of the engineering book and periodicals collections of the Central Colleges of the Phillippines Library - Noces, Maria Juliana M. (2018)
The objectives of this study were to find out the strengths and weaknesses of the engineering book and periodical collections in relation to the PACUCOA and PAARL standards; determine which areas of the engineering course offerings are served most effectively by the book and periodical collections are irrelevant to the curricula. Engineering book and periodical collections were mapped to the 20th edition of the Dewey Decimal Classification system.